System of project multicriteria decision synthesis in construction - Šarka, Vaidotas; Zavadskas, Edmundas K.; Ustinovičius, Leonas; Šarkienė, Edita; Ignatavičius, Česlovas (Technological and Economic Development of Economy, 2008)
The construction industry, compared to other industries, is distinguished by a small productivity of work and large fragmentation. Solution of construction‐related problems requires a great deal of time and financial resources. Method of project multicriteria decision synthesis with decision success criterion is used for realization of construction projects which require analysis of constituent parts in close relationship of components. On every level of the whole project, the decision of closeness to ideal solution method is made and, on the basis of the obtained results, several alternatives are chosen. At the last decision stage, there is performed a synthesis by the chosen alternatives and relying on their interrelations. During decision process on the intermediate stages, having eliminated irrational alternatives, effective and precise results are achieved. The developed multicriteria decision synthesis method is one of the elements of the newly created group of multicriteria decision methods. Using this method algorithm, software is prepared that entirely manages the whole decision process from database filling to calculation and result processing.Projekto daugiatikslių sprendimų sintezės sistema statybojeSantrauka. Straipsnyje nagrinėjamas daugiatikslių sprendimų sintezės metodas ir jo taikymo galimybės. Svarbus investicijų efektyvumo garantas yra projektų analizė ir vertinimas. Tai leidžia pagal tam tikrą rodiklių sistemą nustatyti projekto varianto efektyvumą. Vertinimo rodikliai turi būti grindžiami tiek projektą įgyvendinančio subjekto, tiek investuotojo interesais. Analizuojant projektavimo procesus susiduriama su įvairaus pobūdžio informacija – kokybine ir kiekybine. Čia siūlomas ir aprašomas DSS1 metodas, sprendimų priėmimo etapai, duomenų bazės sudarymo principai. Pateikti metodo taikymo rezultatai.Reišminiai žodžiai: sprendimų paramos sistemos, sintezės metodai, projektai, statyba, integruotisprendiniai.First published online: 21 Oct 2010